Modification, development and application of extraction methods for PAHs in sediments and water - Sibiya, Precious Nokwethemba (My University, 2013)
Polycyclic aromatic hydrocarbons (PAHs) are an important class of persistent organic pollutants (POPs) that are commonly found in the environment at low concentrations. POPs are long-lived organic compounds and originate almost entirely from anthropogenic activities such as chemical industries, combustion and agriculture activities. Owing to their potential carcinogenicity, mutagenicity and teratogenicity, PAHs have been determined in several matrices, particularly water, soil and sediment. Hazards associated with these compounds are owing to their hydrophobic character, persistence and bioaccumulation properties of several individual PAHs. Hence the primary goal of this research was to identify and determine PAHs in water and sediment samples, from rivers and dams in greater Johannesburg area, South Africa. In this work, three extraction techniques have been optimized for the extraction of PAHs in various samples. The extraction techniques based on hollow fiber liquid phase microextraction (HF-LPME) and solid phase extraction (SPE) were optimized for aqueous samples. Microwave assisted extraction technique (MAE) was optimized for solid samples. The optimized methods were applied to real water and sediment samples in and around Johannesburg area. HF-LPME and SPE techniques were compared with each other, while MAE was compared with Soxhlet (SE) in terms of their extraction efficiencies, enrichment factors, detection limits, relative standard deviations and concentrations of PAHs found in real samples. HF-LPME technique involved extraction of PAHs from a 20 mL sample containing 20% acetonitrile as a modifier. The PAHs were extracted into a 5 cm hollow fibre filled with heptane as organic solvent. At a stirring speed and extraction time of 600 rpm and 30 minutes, respectively, the acceptor solvent was collected to be analysed by GC-MS. The obtained enrichment factors ranged from 40 to 95 and the recoveries ranged from 3-8% depending on individual PAHs. The detection limits ranged from 23.0-95.0 ng L-1 while relative standard deviations for the recoveries were less than 5%, (n=3). The concentrations obtained in real water samples ranged from 30.3-213.8 ng L-1 and the relative standard deviations were between 0.8-11.9%, (n=3). SPE technique involved extraction of PAHs from a 100 mL sample containing 10% methanol as a modifier. The PAHs were extracted using C18 cartridges with 40% methanol in water as conditioning solvents and 3 mL acetone: THF (1:1) as eluting solvents. After eluting, the analyte is reduced to 1 mL under nitrogen and then analysed using GC-MS. The obtained enrichment factors ranged from 78-135 depending on the individual PAH. The detection limits ranged from 20.0-52.0 ng L-1. The relative standard deviations for the obtained enrichment factors were less than 6%. The obtained concentrations from real water samples ranged from 21.4-615.7 ng L-1 and the relative standard deviations were between 1.9-13.0%, (n=3). In MAE technique, the extraction was carried out with 20 mL of hexane: acetone (1:1, v/v) mixture with 1 g sample at 250 W for 20 minutes. After extraction, the extract was cleaned and reduced to 1 mL under nitrogen and then injected into an HPLC-Fluoresence system. The obtained recoveries ranged from 61-98% depending on the individual PAHs. The detection limits obtained ranged from 0.03-0.5 μg L-1 for HPLC-Fluorescence. The relative standard deviations were less than 6% for the obtained enrichment factors. The obtained concentrations in the sediments ranged from 61-45281μg kg-1 and the relative standard deviations ranged from 2.1-10.8%, (n=3). The possible major sources of PAHs pollution in rivers and dams in great Johannesburg area was suspected to be due to poor wastewater and solid waste management in informal settlements and a large oil spill accident that happened. This is supported by the large concentrations of PAHs found in sediments from Jukskei River which passes through one of the largest informal settlements. The pH in this river is also basic with large conductivity suggesting the presence of anions. The recipient dam of this river had also problems of algae and weeds growing in it. The influence of oil spill that happened is supported by decreasing concentrations of PAHs in the sediments with distance away from the accident area in the Blaauwpan dam. Other possible sources of PAHs are vehicle emission since studies have shown that from about 2005, the number of these in high ways in the city have been increasing by about 15-20% per year.
Keywords: Polycyclic Aromatic Hydrocarbons.; Sediments.; Water.